Green Accounting as a Pure Moderation: Foreign Ownership on Financial Performance - Purmalastu, Arya Raqli (E-Jurnal Akuntansi; Vol 34 No 8 (2024), 2024)
The research aims to determine the impact of foreign ownership on the financial performance of mining companies which is moderated by the green accounting. This type of research is quantitative research with a descriptive approach. The analysis was carried out using multiple linear regression techniques using IBM SPSS 26. The sample used was sub-industrial mining companies registered on the IDX in 2019-2022, using a purposive sampling method to obtain 24 companies and 96 observation data. Based on the research results, it shows that foreign ownership has an effect on financial performance and green accounting is able to strengthen the influence of foreign ownership on financial performance. Keywords: Green Accounting; Company Performance; Shareholding; Mining Companies.